Understanding Teaching Style Differences and Its Contributions toward Learning Objectives between A Male and A Female Teacher - Kurniawati, Farida Nova; Sonya Maria, Marcella; Syahra Putri, Rizky (JELLT (Journal of English Language and Language Teaching), 2025)
Every teacher has different style to teach their students. Therefore, this research investigates teaching style differences between a male and a female teacher, the development of the students’ learning style from teachers’ teaching style, and its contributions toward learning objectives. This descriptive qualitative research used observation, students’ response journal, field note, and video recording to collect the data. The researcher analyzed the data by using theory from (Grasha, 1996) for analyzing teaching style used by a male and a female teacher. Theory from (Kolb, 1984) was used to analyze learning style of the students. The result shows that there are no significant differences of teaching style used by a male and a female teacher. Converger, accomodator, and diverger are learning styles which are used by the students. The students who have converger and accommodator for their learning style have more active contributions in the classroom. Keywords: Teaching Style, Learning Objectives, Male Teacher, Female Teacher